Washington State Building, Alaska-Yukon-Pacific Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Caption on image: Washington Building Printed on verso: 61. The Washington State Building is an elegant structure of the Modern French School of Architecture, with four massive Ionic columns, to the roof, at the entrance. A magnificant reception room, the finest ever seen at an Exposition, covers the entire ground floor. Publisher: Robert A. Reid (no. 61) PH Coll 78.44 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number